Microchimerism linked to cytotoxic T lymphocyte functional unresponsiveness (clonal anergy) in a tolerant renal transplant recipient - Burlingham, W J; Grailer, A P; Fechner, J H; Kusaka, S; Trucco, M; Kocova, M; Belzer, F O; Sollinger, H W (LIPPINCOTT WILLIAMS & WILKINS, 1995)
A patient was found to be functionally tolerant of a maternal kidney allograft as evidenced by good graft function 5 years after cessation of all immunosuppressive drug therapy. Despite normal in vitro proliferative and IL-2 responses, patient anti-donor 1 degree MLR cultures yielded little donor-specific CTL activity in either bulk or limiting dilution analysis (LDA) cultures. Using polymerase chain reaction, the patient's PBL and skin were found to contain donor-derived Bw6+ cells. Removal of Bw6+ donor cells from the patient PBL with mAb and immunomagnetic beads before stimulation with donor PBL on day 0 failed to restore donor-specific CTL in either bulk 1 degree MLR or LDA cultures. Restimulation of 1 degree cultures with donor stimulator cells plus exogenous IL-2, however, completely restored anti-donor HLA class I-specific CTL, indicating class I-specific CTL precursors were not clonally deleted. Fresh patient PBL, as well as donor cell-enriched fractions, when added at the initiation of 3 degrees MLR cultures, inhibited the generation of anti-donor CTL, whereas donor cell-depleted fractions did not. The inhibition was cell dose-dependent, was specific for the anti-donor response, and was radioresistant (1200 rad). Thus, the clinical tolerance observed in patients with microchimerism may be due to the presence of veto cells within the circulating donor cell pool.